2012
DOI: 10.1017/jgc.2012.28
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Student Access to and Use of Pastoral Care Services in Schools

Abstract: School-based health services (SBHS) including pastoral care can play a pivotal role in addressing adolescent health and wellbeing; including their tobacco and other drug use. To maximise the benefits of these services, they need to be accessible, useful for, and acceptable to students. This formative, qualitative study involved 12 focus groups within nine lower socio-economic Western Australian Government secondary schools. The purpose was to identify student (n = 59) perceptions of the availability and useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Çünkü gün geçtikçe sosyal medya bağımlılığının topluma yönelik zararları ortaya çıkmaktadır. 97 Gençlerin siber zorbalık eylemlerinin önemli ölçüde arttığını, gençlerin birçoğunun günlük olarak, akranlarının moralini bozabilecek mesajlar ve görüntüleri dijital cihazlar vasıtasıyla ve genellikle Facebook, Instagram ve YouTube gibi herkese açık olan sosyal ağ sitelerini kullanarak gönderdikleri görülmektedir. 98 Özellikle sosyal medya bağımlılık durumu yaşayanlar hiçbir çekince olmadan siber zorbalıkta bulunabilmektedirler.…”
Section: Manevi Danışmanlık Nedir?unclassified
“…Çünkü gün geçtikçe sosyal medya bağımlılığının topluma yönelik zararları ortaya çıkmaktadır. 97 Gençlerin siber zorbalık eylemlerinin önemli ölçüde arttığını, gençlerin birçoğunun günlük olarak, akranlarının moralini bozabilecek mesajlar ve görüntüleri dijital cihazlar vasıtasıyla ve genellikle Facebook, Instagram ve YouTube gibi herkese açık olan sosyal ağ sitelerini kullanarak gönderdikleri görülmektedir. 98 Özellikle sosyal medya bağımlılık durumu yaşayanlar hiçbir çekince olmadan siber zorbalıkta bulunabilmektedirler.…”
Section: Manevi Danışmanlık Nedir?unclassified
“…Friendly Schools' research found only 38% of students in Grades 7-9 who were targets of bullying spoke with a school staff member about it, 53% told another adult, and 48% told a friend or sibling (Shaw et al, 2019). This low rate of help seeking was particularly true for students who identify as male, and secondary school students (Cardoso et al, 2012;Lawrence et al, 2015). Our research suggests that school counsellors may need to provide bridging actions, such as initial online contact (particularly for boys), and empower students to accompany bullied students to seek help when they need it.…”
Section: Increasing Help-seeking Behaviourmentioning
confidence: 99%
“…Recent evaluations of school-based health programmes show that the following factors are needed for such interventions to be effective (Macpherson, 2013;Cardoso et al, 2012;UK Department of Health, 2012;Chase et al, 2006):…”
Section: Access To Servicesmentioning
confidence: 99%